Thermal stability of nickel molybdenum electrodeposits - -, Suryanto; Ani, Mohd Hanafi (Trans Tech Publications, Switzerland, 2012)
Thermal stability of nickel molybdenum electrodeposits was investigated. This investigation is important to show that electrodeposits can be used at elevated temperature and to understand electrodeposit behaviour as a function of temperature. Crack-free electrodeposits with up to 17 at% molybdenum were produced by the square pulse electro-deposition technique from a solution containing nickel sulphamate. The experiment was performed using vacuum furnace. Microstructure of deposits was investigated using microscope SEM, while the phase of deposits was studied using x-ray diffraction. Chemical composition of deposits was observed using energy dispersive x-ray analyzer and hardness of deposits was measured using micro hardness tester. The result shows that nickel molybdenum electrodeposits stable up to 400 oC. For 550 oC, grain growth was observed to start but the hardness of electrodeposits has no significant changed. Hardness analysis shows that hardness of electrodeposits does follow Hall Petch relationship.